Determinan Kualitas Laporan Keuangan Pada Perusahaan Di Indonesia Dan Implikasinya Terhadap Nilai Perusahaan Di Era Revolusi Industri 4.0 - Junita Putri Rajana Harahap; Reza Hanafi Lubis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The value of the company represents a picture of the state of the company whether it is in good or bad condition. The value of the company can affect the views of investors in making decisions to invest. One way that can be used to see the good or bad value of a company is to assess the quality of the company's financial statements. The quality of financial reports in this study is seen from several aspects of earnings management, namely the Loss Avoidance Ratio (LAR), Profit Decline Avoidance Ratio (PDAR), and the Quality Audit Opinion Ratio (QAOR). In addition, this study also uses the KAP Criteria Ratio - Big Four / Non Big Four Ratio (NBAR) in seeing its effect on company value. The research focuses on companies listed on the Indonesia Stock Exchange except for companies in the financial sector. The method used in this study is a descriptive method using a quantitative approach. The results showed that only the Profit Decrease Ratio (PDAR) had an effect on firm value, while the loss ratio (LAR), audit opinion quality ratio (QAOR) and KAP criteria ratio (NBAR) had no effect on firm value.